2017
DOI: 10.1002/2016wr020126
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of glacier ablation acrossNorth‐CentralChile: Identifying the limits of empirical melt models under sublimation‐favorable conditions

Abstract: We investigate the energy balance and ablation regimes of glaciers in high‐elevation, dry environments using glaciometeorological data collected on six glaciers in the semiarid Andes of North‐Central Chile (29–34°S, 3127–5324 m). We use a point‐scale physically based energy balance (EB) model and an enhanced Temperature‐Index (ETI) model that calculates melt rates only as a function of air temperature and net shortwave radiation. At all sites, the largest energy inputs are net shortwave and incoming longwave r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 100 publications
(206 reference statements)
3
40
0
Order By: Relevance
“…A special case is that of dry mountains with sporadic snowfall that is retained due to generally cold temperatures, such as in the very high elevation but largely arid Andes (MacDonell, Kinnard, Molg, Nicholson, & Abermann, 2013). Sublimation plays a key role in snow ablation, occurring yearround under the influence of solar radiation and wind (Ayala, Pellicciotti, MacDonell, McPhee, & Burlando, 2017;Gascoin, Lhermitte, Kinnard, Bortels, & Liston, 2013). In general, sublimation is a potentially important driver of snow ablation in drier climates (see, for example, the review on Mediterranean snow hydrology by Fayad et al (2017b)), and in cold and windy climates (due to the stronger sublimation of blowing snow (Law & Vandijk, 1994)), for example, in many high-elevation and high-latitude regions such as the Canadian Rocky Mountains (MacDonald, Pomeroy, & Pietroniro, 2010).…”
Section: Snow Regions Of the Worldmentioning
confidence: 99%
“…A special case is that of dry mountains with sporadic snowfall that is retained due to generally cold temperatures, such as in the very high elevation but largely arid Andes (MacDonell, Kinnard, Molg, Nicholson, & Abermann, 2013). Sublimation plays a key role in snow ablation, occurring yearround under the influence of solar radiation and wind (Ayala, Pellicciotti, MacDonell, McPhee, & Burlando, 2017;Gascoin, Lhermitte, Kinnard, Bortels, & Liston, 2013). In general, sublimation is a potentially important driver of snow ablation in drier climates (see, for example, the review on Mediterranean snow hydrology by Fayad et al (2017b)), and in cold and windy climates (due to the stronger sublimation of blowing snow (Law & Vandijk, 1994)), for example, in many high-elevation and high-latitude regions such as the Canadian Rocky Mountains (MacDonald, Pomeroy, & Pietroniro, 2010).…”
Section: Snow Regions Of the Worldmentioning
confidence: 99%
“…We choose a set of model parameters typically used in the literature for this region (Ragettli and Pellicciotti, 2012;Ayala et al, 2016;Burger et al, 2018a) for all individual glacier models and keep parameter calibration at a minimum level. For each glacier, we vary only the ETI model parameters within ranges suggested in the literature (Finger et al, 2011;Ragettli and Pellicciotti, 2012;Ayala et al, 2017a) to fit the glacier-wide mass balance as derived from the geodetic mass balances. A summary of literature-derived and calibrated parameters for the individual models is shown in Table 1.…”
Section: Model Setup For Individual Glaciers 295mentioning
confidence: 99%
“…In relation to TOPKAPI-ETH, it has been shown that the parameterizations of snow accumulation and ablation included in 530 TOPKAPI-ETH work well for wind-sheltered locations (Ayala et al, 2017a). However, the representation of processes driving the mass balance at some specific sites requires more fundamental work, and additional parameterizations or more physicallybased representations are required.…”
Section: Uncertainties In the Modelling Of Glacier Changes In Data-scmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial heterogeneity of the snow cover can be attributed to local precipitation events that are strongly affected by the interaction of the terrain elevation with the local climate (Mott et al, ). The preferential distribution of initial snow cover on favorable slopes and aspects may be subsequently redistributed by wind (Essery et al, ; Gascoin et al, ; Lehning et al, ; Schirmer & Lehning, ; Trujillo et al, ) or avalanching (Bernhardt & Schulz, ; Ragettli et al, ), thus adjusting the shape of the seasonal hydrograph (Freudiger et al, ), the potential melt‐sublimation ratio (Ayala et al, ), and the mass balance of glacierized basins (Gascoin et al, ; McGrath et al, ). Furthermore, the resulting spatial snow distribution can be governed by the radiation forcing of the surface slope relative to the local solar zenith and azimuth angle of the sun (Ayala et al, ), promoting higher quantities of snow on north‐facing slopes (in the Northern Hemisphere), and delaying melt onset.…”
Section: Introductionmentioning
confidence: 99%